Електрична активність кори головного мозку та поверхневих м’язів пальців у жінок із високою і низькою індивідуальною α-частотою - Моренко, Алевтина; Morenko, Alevtyna (Східноєвропейський національний університет імені Лесі Українки, 2014)
113 здорових жінок за значенням медіани (me = 10,29 Гц) індивідуальної α-частоти (ІАЧ) було поділено на групи з високим і низьким рівнями ІАЧ. У жінок із високою ІАЧ вищий активаційний тонус кори пов’я¬заний із більшими латеральними відмінностями активності дистальних м’язів кисті, з низькою ІАЧ – виявлено підвищення напруженості мозкових процесів. A test group consisting of 113 healthy women from the ages of 19 to 21 was divided into two groups according to the magnitude of their individual EEG α-frequency (ІАF) median – groups with high (n = 59, IA ≥ 10,29 Hz) and low (n = 54, IAF < 10,29 Hz) levels of ІАF. Differences between the groups in terms of the power and coherence of EEG oscillations and the EMG signal average amplitude and frequency at rest were estimated. Іnstalled features of power and coherence of EEG oscillations indicate a higher cortex activation tone in women with high IAF. The result of such cerebral processes is the large lateral and reciprocal asymmetry of supra¬spinal effects on the neuromuscular periphery. In contrast, a lower functional state of the cortex offset the increasing intensity of brain processes that can be modulated by the limbic system in women with low IAF. Under these conditions, marked by smaller lateral specificity in the downstream impacts on the muscles of fingers of the right and left hands.
Electrical Activity of the Cerebral Cortex and Superficial Muscles of the Fingers in Women Having High or Low Individual α-Frequency
Keywords: стан функціонального спокою; індивідуальна альфа-частота; потужність і когерентність електроенцефалограми; тонус м’язів; functional status of rest; individual alpha-frequency; electroencephalogram power and coherency; muscle tone